Distributed poly-square mapping for large-scale semi-structured quad mesh generation. (September 2017) - Liu, Celong; Yu, Wuyi; Chen, Zhonggui; Li, Xin
Abstract: We develop a distributed poly-square mapping algorithm for large-scale 2D geometric regions, which is suitable for generating huge quadrilateral meshes in parallel using computer clusters. Our approach adopts a divide-and-conquer strategy based on domain decomposition. We first partition the data into solvable subregions, balancing their size, geometry, and communication cost; then, poly-square maps will be solved on subregions; these maps are finally merged and optimized globally through a multi-pass optimization algorithm. We demonstrate that our meshing framework can handle very big and complex geometric datasets using high performance clusters efficiently and generate high-quality semi-structured quad meshes. Highlights: A new distributed poly-square mapping (DPSM) algorithm for parallel parameterization of extremely big and complex 2D geometries. A poly-square parameterization that supports the introduction of interior singularities to reduce mapping distortion. A distributed and parallel semi-structured meshing algorithm for complex 2D geometries, with good scalability, iterative layout refinement. Graphical abstract: